AIAA/AAS Astrodynamics Specialist Conference 2016
DOI: 10.2514/6.2016-5269
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Capture of a Resident Space Object by a Spacecraft with a Robotic Manipulator: Analysis, Simulation and Experiments

Abstract: This paper describes a set of laboratory-based experiments, which demonstrate the autonomous capture of a non-moving resident space object by a spacecraft equipped with a single robotic manipulator. An air bearing test bed is used to simulate weightlessness and frictionless maneuvering on a plane. The chaser is composed by a floating spacecraft simulator carrying a kinematically redundant four-link serial manipulator. The manipulator mass is similar to the mass of its base-spacecraft, resulting in an unusually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…1 for an overview of the experimental setup. The experiments presented here are a continuation of an earlier set of experiments conducted by the authors in the POSEIDYN test bed [22]. Previously flown and experimentally tested spacecraft-manipulator systems have exhibited substantially more benign mass and inertia ratios than the ones found in the spacecraft-manipulator system used for this set of experiments.…”
Section: E-mail Address: Jvirgili@npsedu (J Virgili-llop)supporting
confidence: 48%
See 1 more Smart Citation
“…1 for an overview of the experimental setup. The experiments presented here are a continuation of an earlier set of experiments conducted by the authors in the POSEIDYN test bed [22]. Previously flown and experimentally tested spacecraft-manipulator systems have exhibited substantially more benign mass and inertia ratios than the ones found in the spacecraft-manipulator system used for this set of experiments.…”
Section: E-mail Address: Jvirgili@npsedu (J Virgili-llop)supporting
confidence: 48%
“…Another option to simplify the system is to formulate the equations of motion from the system's center-of-mass [22], directly obtaining a linear system. The performance measure of an infinite-horizon LQR can be written as in Eq.…”
Section: Hold State Tolerance X Tolmentioning
confidence: 99%
“…This differs from existing techniques due to the fact that it includes the possibility to constrain the final velocity of the EE by making the period of the capture maneuver an optimization variable. Virgili-Llop et al [19,20] described a set of laboratory-based experiments using a free-floating robot in which they demonstrated the autonomous capture of a nonmoving space object using a robotic manipulator. The authors made use of the Proximity Operation of Spacecraft: Experimental hardware-In-the-loop DYNamic Simulator testing platform [21], which can create a quasi-frictionless planar environment.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of the presented experimental demonstration surpasses previous experimental work known to the authors, significantly advancing the demonstrated state-of-the-art related to the capture of tumbling RSOs by spacecraft equipped with robotic manipulators. Previous work using planar air bearing test beds (Schwartz et al, 2003) includes Alexander and Cannon (1989), Umetani and Yoshida (1989), Ullman and Cannon (1993), Chen and Cannon (1994), Russakow et al (1995), Yoshida (1994), Nahon et al (1995), Menon et al (2007), Toglia et al (2011), Wilde et al (2016), Virgili-Llop et al (2016b), and Sabatini et al (2017). Other relevant experimental work on orbit or on other types of experimental facilities (Xu et al, 2011) includes Oda et al (1996), Ogilvie et al (2008), Aghili (2008), Xu et al (2009), and Persson and Sharf (2015) among others.…”
Section: Introductionmentioning
confidence: 99%